Multidimensional Impacts of Nickel Mining Exploitation towards the Lives of the Local Community - Karsadi Karsadi; La Aso (Jurnal Ilmu Sosial dan Humaniora, 2023)
The mining companies’ activities caused problems in the community. This research aims to analyze the impact caused by mining activities on the lives of local communities. The research location was in Mandiodo Village, North Konawe Regency. This research used a qualitative approach, and data was collected through observation and in-depth interviews with several community leaders and village government officials. The collected data were analyzed descriptively. The study results show that mining activities negatively impact the social, economic, and environmental lives of local communities in Mandiodo village. Nevertheless, a positive impact can be seen from the increase in the income of some people due to the diversification of the community's economic businesses: boarding house rental services, basic food stalls, and the opening of new jobs for local people to work in companies, as well as acculturation between immigrant and local communities. On the other hand, negative impacts are detrimental to local communities: flooding in residential areas during heavy rains and the threat of landslides, air pollution which can cause various respiratory tract infections, siltation of beaches and seawater pollution, decreased fishermen's income, and damaged roads and bridges. Efforts to overcome the company's negative impacts have not been appropriate because the compensation and recognition the company has provided to the community are not commensurate with the negative impacts that are still detrimental to local communities. The conclusion is that the existence of mining companies causes disasters and losses for local communities.